Investigation of the link between obesity and breast cancer - the role of adipose tissue in the development and propagation of malignancy - Carroll, Paul Anthony (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2010)
Obesity and the metabolic syndrome are emerging risk factors for breast cancer. They are associated with increased incidence, an increased recurrence rate and a poorer prognosis. Despite this epidemiological evidence to suggest the associations between the two, very little data is forthcoming regarding the molecular mechanisms to link obesity with breast cancer. Adipose tissue is known to produce various chemokines, cytokines and peptides, collectively called ‘adipokines’. The production of these adipokines is direcdy related to obesity status. In particular, leptin and adiponectin have stimulated great interest as their biological and pathophysiological properties are largely in opposition to one another. Furthermore it is postulated they function in an endocrine, paracrine or autocrine pathway to influence aspects of cancer progression. We hypothesise that adipokines are produced by mammary adipose tissue and that obesity status influences the production of these growth factors. We further propose that obesity status influences adipokine expression in human breast cancer tumour tissue.
Keywords: Surgery, M.D.; M.D. Trinity College Dublin